2019
DOI: 10.3390/ijms20246156
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarthritis and Cartilage Regeneration: Focus on Pathophysiology and Molecular Mechanisms

Abstract: Osteoarthritis (OA) is a leading cause of disability and source of societal cost in older adults [...]

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 43 publications
3
17
0
Order By: Relevance
“…Growth and molecular function proteins. Growth and molecular function-related proteins not only play important roles in cell and tissue growth but are also important for cartilage regeneration related to OA (28,29) In the present study, we identified 4 and 114 proteins related to growth and molecular functions, respectively, and we confirmed that their expression levels were increased or decreased in the ICRS3 group compared with the ICRS1 group. Metallothionein-2 (MT2A; -log 1.00-fold), metallothionein-1X (MT1X; -log 1.32-fold), argininosuccinate synthase (ASS1; -log 1.32-fold), isoform 2 of N-acetlymuramoyl-L-alanine amidase (PGLYRP2; -log 1.74-fold) and CD59 glycoprotein (CD59; -log 1.74-fold) were increased in the ICRS3 group compared with the ICRS1 group.…”
Section: Icrs Gradesupporting
confidence: 74%
“…Growth and molecular function proteins. Growth and molecular function-related proteins not only play important roles in cell and tissue growth but are also important for cartilage regeneration related to OA (28,29) In the present study, we identified 4 and 114 proteins related to growth and molecular functions, respectively, and we confirmed that their expression levels were increased or decreased in the ICRS3 group compared with the ICRS1 group. Metallothionein-2 (MT2A; -log 1.00-fold), metallothionein-1X (MT1X; -log 1.32-fold), argininosuccinate synthase (ASS1; -log 1.32-fold), isoform 2 of N-acetlymuramoyl-L-alanine amidase (PGLYRP2; -log 1.74-fold) and CD59 glycoprotein (CD59; -log 1.74-fold) were increased in the ICRS3 group compared with the ICRS1 group.…”
Section: Icrs Gradesupporting
confidence: 74%
“…OA is classified as a degenerative joint disease, affecting the whole joint with all its tissue components. Functional and structural changes occur in multiple joint tissues and result in damage and loss of cartilage and the remodeling of subchondral bone resulting in pain as the most disabling symptom for the patient ( Litwic et al, 2013 ; Grässel and Aszodi, 2019 ). OP is characterized by an imbalance of bone formation and resorption, thereby affecting the integration of bone density and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the common osteoarthritis risk factors might instigate a different mechanistic pathway leading to osteoarthritis. A number of strati cations have been proposed on the basis of speci c pathological processes to classify different mechanistic subgroups, which include an increased in ammatory component, mechanical overload, metabolic alterations, and cell senescence [37]. Knowledge of the heterogeneity of OA would help better de ne potential treatment targets, improve the ability to select appropriate patients for future clinical interventions and adapt outcome measures to the situation [38].…”
Section: Identi Cation and Characterization Of Molecular Subgroupsmentioning
confidence: 99%